ANALYSIS OF RECEPTIONIST SERVICE QUALITY FOR THE TOURISTS’ SATIFACTION AT THE GRAND INNA HOTEL KUTA - Ni Kadek Tuwin Patriani; I Gusti Agung Bagus Mataram; I Made Darma Oka; I Ketut Sadia (Politeknik Negeri Bali, 2018)
This research is motivated by the receptionist role known as the first and last impression of the guest. Quality of service is the thing that affects customer satisfaction. This research is aimed at knowing how the receptionist’s service quality towards customer satisfaction in Grand Inna Kuta. The data was collected through the distribution of questionnaires. While, the technique of sampling applied was incidental sampling of 85 respondents. The data was analyzed using multiple linear regression with SPSS 20 software through the techniques of validity and reliability, and importance performance analysis. The results show that in general the assessment of guests staying at the Grand Inna Kuta hotel, regarding the quality of receptionist services at the hotel, can be satisfactory. This can be shown from the analysis where the average value of perception is 3.9. Indicator that make good perception is able to answer questions, able to give clear and easy to understand information, completeness and readiness of receptionist staff, knowledge of existing facilities at Grand Inna Kuta, ability of staff to quickly respond to problems of tourist complaints, general knowledge about Bali, hospitality of receptionist staff, timeliness, ease of receptionist staff to be met, helpful, politeness of receptionist staff, language mastery and courtesy of the reception staff. Indicator that formed a bad perception is the timeliness of the receptionist staff in serving the guests